Pendidikan Keaksaraan sebagai Solusi Mengatasi Buta Aksara pada Masyarakat - Rara Insani; Solfema Solfema; Lili Dasa Putri (Pusat Riset dan Inovasi Nasional, 2024)
One form of Non-Formal Education service that is very useful for the community is a literacy education program. The aim of this program is to help illiterate citizens develop their writing, reading, arithmetic and analytical thinking skills. This program is designed to be relevant to their daily lives, by exploiting the potential that exists around them. In this way, citizens learn and society can improve their quality of life in various situations. Literacy education plays an important role in maintaining the rights of people who are unable to obtain formal education to be able to obtain quality education, as well as providing opportunities for them to develop a better life through the knowledge and knowledge they have. Literacy Education is one of the programs organized by the government to reduce the number of people who cannot read and write in Indonesia. The existence of literacy programs has a clear reason, because it can help people who have difficulty or do not have basic knowledge about reading and writing to develop these abilities. This not only provides benefits to individuals, groups or communities, but can also have a positive impact on their economy. This program plays a role in improving the quality of human resources for our country. Therefore, it is very important to apply literacy education to all communities around us. This program will bring benefits to society in the future.